(untitled) (LEGAL DIALOGICA, 2025)
This study aims to examine the efforts made by law enforcement officers of the Makassar Metropolitan Police in addressing the criminal act of assault (mob violence) that occurs in nightlife entertainment venues, as well as to identify the factors that contribute to the occurrence of such criminal acts in these locations. This study employs an empirical legal research method conducted at the Makassar Metropolitan Police Office. By using the empirical legal research method, the author considers that the Makassar Metropolitan Police Office possesses concrete and accurate data obtained during their operations within the jurisdiction of the Makassar Metropolitan Police. Furthermore, the Makassar City Police is an institution that is indeed within the scope of handling criminal activities, particularly those occurring in nightlife entertainment venues in the city of Makassar. The The results of the study show that nightlife entertainment venues are the primary locations where incidents of assault and battery occur. Regarding the contributing factors, they are divided into two categories: internal factors and external factors. The internal factors include education and family background, while the external factor is the surrounding environment. Therefore, the operations conducted over the past four years (2021, 2022, 2023, 2024) have reflected the number of cases that have occurred. Based on this, the researcher suggests that the police should intensify their efforts in conducting operations for security and enforcement in nightlife entertainment venues and other similar places, so that even the smallest criminal acts can be detected. Keywords: Assault, Nightlife Entertainment Venues Abstrak: Penelitian ini bertujuan untuk mengetahui upaya aparat penegak hukum polrestabes Makassar dalam menanggulangi tindak pidana pengeroyokan yang terjadi di tempat hiburan malam dan faktor – faktor apa saja yang menyebabkan terjadinya tindak pidana pengeroyokan di tempat hiburan malam. Penelitian ini menggunakan metode penelitian hukum empiris yang melakukan penelitian di Kantor Kepolisian Kota Besar Makassar. Dengan metode penelitian hukum empiris . Penulis memiliki pertimbangan bahwa Kantor Kepolisian Kota Besar Makassar memiliki data yang konkrit dan akurat sesuai yang mereka jaring pada saat mereka melakukan operasi di Wilayah Hukum Polrestabes Makassar dan Polres kota Makassaar merupakan institusi yang memang sudah menjadi ranah dalam kejahatan terutamanya di tempat hiburan malam di kota Makassar Hasil penelitian menunjukkan bahwa tempat hiburan malam yang menjadi basis terjadinya pengeroyokan, penganiayaan dan Adapun tentang masalah faktor , faktor terdiri menjadi 2 bagian yaitu faktor intern dan faktor eksternal Adapun faktor internal yaitu faktor Pendidikan dan faktor keluarga sedangkan faktor eksternal ialah faktor lingkungan. Oleh karena itu operasi yang dilakukan pada empat tahun terakhir (2021,2022,2023,2024) menunjukkan jumlah kasus yang terjadi. Kemudian saran peneliti, untuk pihak kepolisian agar kiranya lebih giat lagi dalam melakukan operasi dalam pengamanan maupun penertiban dalam tempat hiburan malam dan lain-lain agar kejahatan se kecil apapun dapat terdeteksi. Kata Kunci : Pengeroyokan, Tempat Hiburan Malam